The Medicago truncatula ortholog of Arabidopsis EIN2, sickle, is a negative regulator of symbiotic and pathogenic microbial associations - Penmetsa, R.; Uribe, P.; Anderson, J.; Lichtenzveig, Judith; Gish, John-Charles; Nam, Young Woo; Engstrom, Eric; Xu, Kun; Sckisel, Gail; Pereira, Mariana; Baek, Jong Min; Lopez-Meyer, Melina; et al. (Wiley, 2008)
The plant hormone ethylene negatively regulates bacterial infection and nodule formation in legumes in response to symbiotic rhizobia, but the molecular mechanism(s) of ethylene action in symbiosis remain obscure. We have identified and characterized multiple mutant alleles of the MtSkl1 gene, which controls both ethylene sensitivity and nodule numbers. We show that this locus encodes the Medicago truncatula ortholog of the Arabidopsis ethylene signaling protein EIN2. In addition to the well-characterized role of MtSkl1 in rhizobial symbiosis, we show that MtSkl1 is involved in regulating early phases of the symbiotic interaction with mycorrhizal fungi, and in mediating root responses to cytokinin. MtSkl1 also functions in the defense against Rhizoctonia solani and Phytophthora medicaginis, with the latter interaction likely to involve positive feedback amplification of ethylene biosynthesis. Overexpression of the C-terminal domain of MtEIN2 is sufficient to block nodulation responses, consistent with previous reports in Arabidopsis on the activation of ethylene signaling. This same C-terminal region is uniquely conserved throughout the EIN2 homologs of angiosperms, which is consistent with its role as a higher plant-specific innovation essential to EIN2 function.